2011
DOI: 10.1159/000324373
|View full text |Cite
|
Sign up to set email alerts
|

Depletion of Plasma Gelsolin in Patients with Tick-Borne Encephalitis and Lyme Neuroborreliosis

Abstract: Background/Aims: Cell damage during the course of inflammation results in cytoplasmic actin release, which if not eliminated by the extracellular actin scavenger system, composed of gelsolin and vitamin D binding protein, can cause dysfunction of hemostasis and toxicity towards surrounding cells. In this study, we test the hypothesis that an inflammatory reaction induced by central nervous system infections such as tick-borne encephalitis (TBE) or Lyme neuroborreliosis (LNB) will result in plasma gelsolin conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 55 publications
0
12
0
Order By: Relevance
“…A number of studies suggest the neuroprotective role of gelsolin and potential of hypogelsolinemia as a therapeutic target in the development for therapeutic interventions in some neurological illnesses, including ischemic stroke [ 133 ], Alzheimer’s disease [ 134 ], multiple sclerosis [ 67 ], tick-borne encephalitis and Lyme neuroborreliosis [ 66 ], and subarachnoid hemorrhage [ 135 ]. Furukawa et al and Endres et al, using gelsolin knock-out mice, demonstrated that gelsolin protects neurons against excitotoxic Ca 2+ overload via modulation of calcium influx through N-methyl-D-aspartate (NMDA) receptors and voltage-dependent Ca 2+ channels (VDCC) in hippocampal neurons.…”
Section: Alterations In Plasma Gelsolin Concentrations In Differenmentioning
confidence: 99%
“…A number of studies suggest the neuroprotective role of gelsolin and potential of hypogelsolinemia as a therapeutic target in the development for therapeutic interventions in some neurological illnesses, including ischemic stroke [ 133 ], Alzheimer’s disease [ 134 ], multiple sclerosis [ 67 ], tick-borne encephalitis and Lyme neuroborreliosis [ 66 ], and subarachnoid hemorrhage [ 135 ]. Furukawa et al and Endres et al, using gelsolin knock-out mice, demonstrated that gelsolin protects neurons against excitotoxic Ca 2+ overload via modulation of calcium influx through N-methyl-D-aspartate (NMDA) receptors and voltage-dependent Ca 2+ channels (VDCC) in hippocampal neurons.…”
Section: Alterations In Plasma Gelsolin Concentrations In Differenmentioning
confidence: 99%
“…The G-actin-gelsolin and G-actin-Gc-globulin complexes are primarily removed from the circulation by mononuclear phagocytes. 3,4 Low concentrations of Gc-globulin correspond to a poor prognostic outlook in acute liver failure, multiple organ dysfunction syndrome and sepsis. 5,6 Gc-globulin is also involved in the transport of vitamin D with its metabolites, fatty acids and endotoxins, functions in the activation of osteoclasts and macrophages, and serves as a chemotactic cue for leukocytes.…”
Section: Introductionmentioning
confidence: 99%
“…These results suggest that the S1P pathway may partly govern the production of pro-inflammatory cytokines by astrocytes. Consequently, it is highly probable that the potential therapeutic effects of GSN (which has a significantly decreased concentration in the blood of TBE patients [ 45 ]) and FTY720P might be caused by modulation of S1P-mediated activation of astrocytes in the CNS. It was recently reported that FTY720 exposure might regulate specific neuroinflammatory responses by desensitizing astrocytes to external S1P [ 19 ].…”
Section: Resultsmentioning
confidence: 99%